Evaluasi Sistem Pengelolaan Rekam Medis Pasien Rawat Inap Study Kualitatif di RSKIA UMI KHASANAH - Tri Tri Ariani; Eny Retna Ambarwati; Wiyadi Wiyadi (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
ABSTRACTGood management of medical records to support hospital services and useful if the information contained therein is complete and accurate. Medical record data is needed in the process of recording and reporting routine hospitals. The purpose of this research is to treat and manage medical records of inpatients at RSKIA Umi Khasanah Bantul. descriptive research with a qualitative approach. Research subjects Director, medical record personnel, midwives and doctors. Data collection using in-depth interview techniques supported by documentation. Data analysis technique with reduction, presentation, conclusion. The results of the patient's medical research using a manual system. Medical records are more than 2 x 24 hours because the medical record documents are not completely filled, the storage space is not sufficient, the SOP for medical records is not complete, the length of providing medical records according to the law is <15 minutes, supervision medical records seen from the assessment indicators. The problem is that there is still a lack of medical record personnel, insufficient infrastructure.Keywords: Evaluation, Management, Medical Records